Socio-Economic Impact of Human-Wildlife Conflicts on Agriculture based Livelihood in the Kodagu Karanataka State - Karthik; Prathiba, K (International Journal of Engineering and Management Research, 2025)
Human-wildlife conflicts (HWC) pose significant socio-economic challenges for agriculture-based livelihoods in Kodagu, Karnataka. This study examines the extent and impact of wildlife-related damages on crops, livestock, and farmer well-being, focusing on economic losses, food security, and coping mechanisms. Kodagu, known for its rich biodiversity and proximity to protected areas, experiences frequent conflicts with elephants, wild boars, and other species, leading to substantial financial strain on farmers. Additionally, psychological stress and rural migration trends further exacerbate socio-economic instability. The study highlights the effectiveness of existing mitigation strategies, including compensation schemes, fencing, and community-based conservation efforts. Policy recommendations emphasize the need for sustainable, long-term conflict resolution strategies to balance conservation goals with farmers’ livelihoods.